2014
DOI: 10.3892/ijmm.2014.1947
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized S100A4 inhibits the activation of protein phosphatase 5 through S100A1 in MKN-45 gastric carcinoma cells

Abstract: Abstract. S100 proteins bind to numerous target proteins, as well as other S100 proteins and activate signaling cascades. S100 proteins can be modified by various post-translational modifications, such as phosphorylation, methylation and acetylation. In addition, oxidation is important for modulating their activities. Previous studies have shown that S100A1 interacts with S100A4 in vitro and in vivo. Due to this potential cross-talk among the S100 proteins, the aim of the present study was to examine whether S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The overexpression of S100A4 decreases the sensitivity of HT29 colon cancer human cells to methotrexate, whereas its knockdown causes chemosensitization towards methotrexate ( 27 ). Considering the interaction of S100A1 with S100A4 and their regulatory association ( 13 , 14 , 28 , 29 ), it is likely that S100A1 sensitizes HCC cells to DDP through S100A4.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of S100A4 decreases the sensitivity of HT29 colon cancer human cells to methotrexate, whereas its knockdown causes chemosensitization towards methotrexate ( 27 ). Considering the interaction of S100A1 with S100A4 and their regulatory association ( 13 , 14 , 28 , 29 ), it is likely that S100A1 sensitizes HCC cells to DDP through S100A4.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Moreover, cysteine residues at the dimer surface of S100A4 in the extracellular space may form disulfide bonds when they are oxidized. 48,49 Despite the wealth of structural information, our knowledge on the dynamics is quite limited. Insights into the molecular dynamics (MD) of S100A4 and the mechanisms controlling the (dis)assembly of NMIIA may contribute to the design of new inhibitors to disrupt the interaction of S100A4 with NMIIA to prevent the spread of tumor cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, an experimental study found that mutation of the C-terminal EF-hand of S100A4 reduces Ca 2+ binding and cell motility/invasion in vitro and the affinity of the interaction of S100A4 and NMIIA isoform, and metastasis promotion . Another study showed that the C-terminal lysine (residue 101) in wild-type S100A4 increases the rate of association between S100A4 and NMIIA isoform, suggesting that the C-terminal region of S100A4 is an important inhibitor-binding site for its metastasis-inducing properties. , Moreover, cysteine residues at the dimer surface of S100A4 in the extracellular space may form disulfide bonds when they are oxidized. , …”
Section: Introductionmentioning
confidence: 99%
“…Non-oxidized S100A4 is able to bind to protein phosphatase 5 (PP5), whereas the oxidized S100A4 protein disulfide-linked dimers and oligomers directly interacts with the S100A1 that cannot bind to PP5. S100A4 oxidation could be induced by hydrogen peroxide treatment in gastric cancer cells, decreasing S100A4-PP5 interaction and the inhibition of PP5 activation process, which is closely associated with gastric cancer cell malignant phenotypes [ 90 ]. S100A4 can also promote the cancer stem cell (CSC)-like properties in gastric cancer cells by the enhancement of growth differentiation factor 15 (GDF15) expression, i.e., S100A4 binds to the GDF15 promoter to induce CSC-like properties in gastric cancer cells, including the formation of spheroid and soft-agar colonies [ 91 ].…”
Section: Introductionmentioning
confidence: 99%